Mortgage Equity Withdrawal in Australian and Britain - Searle, Beverley A; Smith, S; Wood, G; Parkinson, S; Stoakes, A (My University, 2009)
Across the decade to 2007, a combination of house price appreciation and relaxed credit constraints gave a boost to consumption through the mechanism of mortgage equity withdrawal (MEW). Arguably, this kept developed economies buoyant, even through periods of recession. This paper uses panel data on British and Australian homeowners to show that, notwithstanding its macro-economic effects, such borrowing has far-reaching implications for the micro-economy of households. The data indicate that, for the period 2001–2005, equity borrowing was a common tactic. The sums involved were not trivial, were not limited to older cohorts, or the province simply of the rich. In fact, the events and circumstances associated with equity borrowing at the zenith of the last housing cycle were consistent with an insurance, as well as a general consumption, role for MEW. As house prices fall and credit constraints are re-introduced, the options for such borrowing will shrink. Recent financial shocks may, by reducing the availability of a key channel from housing wealth into consumption, prompt a crisis of welfare. They pose challenges for housing and social policy as well as for economic management.
European Journal of Housing Policy
Keywords: Housing -- Equity (including use of); Housing; Housing, communities and neighbourhoods; Housing; Equity (including use of); Housing, community and neighbourhoods